Food security in African Canadian communities: a scoping review. Issue 1 (18th January 2022) - Jefferies, Keisha; Richards, Tiffany; Blinn, Nicole; Sim, Meaghan; Kirk, Sara F.L.; Dhami, Gurneet; Helwig, Melissa; Iduye, Damilola; Moody, Elaine; Macdonald, Marilyn; Tomblin Murphy, Gail; Martin-Misener, Ruth
ABSTRACT: Objective: The objective of this review is to chart the evidence relating to food security among African Canadian communities to inform future research and offer insight related to food security in African Canadian communities. Introduction: Achieving food security is of global importance to meet the United Nations Sustainable Development Goals. As a social determinant of health, food security, which refers to the unrestricted physical, economic, and timely access to safe and nutritious foods, impacts more than 4 million Canadians. Yet, little is known about food security and the differential impacts of food insecurity among African Canadians. This scoping review sought to describe the current state of food security among African Canadians. Inclusion criteria: Sources were considered for inclusion if they: i) focused on Canada, ii) involved African Canadians, and iii) examined food security. Methods: This scoping review was conducted in accordance with JBI methodology. Databases and relevant websites containing peer-reviewed, unpublished, and gray literature were searched. Ancestry searching and forward citation tracing were completed. No restrictions were placed on date of publication. Language restrictions were limited to English and French. In instances where articles were unavailable, authors of potential sources were contacted at the full-text review phase to request access to their article. Data were extracted independently by two team members, and are presented narratively and in tabular format. Results: The search of databases yielded a total of 1183 records. Ancestry tracing yielded 287 records. After removing duplicates, 1075 titles and abstracts were screened for eligibility and 80 advanced to full-text screening. Seventy-five full-text articles were excluded for not meeting the inclusion criteria, leaving five articles that underwent data extraction. All five included studies involved African Canadian participants in Canada. All studies focused on adults; one study included women and men participants, while four focused exclusively on women. One study involving women participants included cisgender and transgender women as well as those identifying as queer. Study designs reflected qualitative (n = 2), quantitative (n = 1), and mixed methods (n = 2) designs. Conclusions: This review begins to fill a gap in understanding the current evidence available on food security as it impacts African Canadians. The findings of this review represent existing research, describing the type of evidence available and methodologies used, before suggesting implications for research and practice. The inclusion of only five studies reveals the limited evidence regarding the current state of food security among African Canadians. Further, included studies were exclusively conducted in urban settings and predominantly in one province. There is a need for further research in rural communities, in other provinces and territories, as well as with younger and older participants. The urgent need to collect race-disaggregated data in Canada is evident.